2022
DOI: 10.1002/ece3.9163
|View full text |Cite
|
Sign up to set email alerts
|

Food quantity and quality shapes reproductive strategies of Daphnia

Abstract: In freshwater environments, one of the challenges aquatic grazers face are periods of suboptimal food quantity and quality. In a life table experiment, the effects of food quantity (a gradient of algae concentration) and quality (a diet of cyanobacteria) on the life histories and resource allocation strategy in Daphnia magna were tested. Growth‐related traits were similarly affected under different food regimes while the reproductive strategies differed in animals exposed to low food qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…In comparison to rotifers fed with low and middle N-containing algae, those fed with high N diets matured faster and advanced their peak and end reproduction times. This finding is consistent with a previous report, which indicated that animals on an unrestricted diet reproduced earlier than those on a strongly restricted diet of green algae Acutodesmus obliquus (Bednarska 2022). High N-containing algal food (≥A 5 ) shortened the prereproductive and reproductive periods of R. rotatoria compared to low (A 0.5 ) or N-free (A 0 ) algal food, but the post-reproductive period was lengthened first and then shortened with increased N concentration in the medium.…”
Section: Discussionsupporting
confidence: 94%
“…In comparison to rotifers fed with low and middle N-containing algae, those fed with high N diets matured faster and advanced their peak and end reproduction times. This finding is consistent with a previous report, which indicated that animals on an unrestricted diet reproduced earlier than those on a strongly restricted diet of green algae Acutodesmus obliquus (Bednarska 2022). High N-containing algal food (≥A 5 ) shortened the prereproductive and reproductive periods of R. rotatoria compared to low (A 0.5 ) or N-free (A 0 ) algal food, but the post-reproductive period was lengthened first and then shortened with increased N concentration in the medium.…”
Section: Discussionsupporting
confidence: 94%
“…Daphniids are often considered the most suitable zooplankton to control cyanobacterial blooms. The large body size and adequate growth rates of Daphnia magna on cyanobacterial diets [ 19 ] indicate that the species is ideally suited for lake management. This is probably the reason for the emphasis on studies on Daphnia ; nineteen species of the genus Daphnia have been used in experiments to test the effects of cyanobacteria or cyanotoxins on their fitness, while thirteen species of all the other cladocerans have been used in similar studies ( Table 2 ).…”
Section: Attempts To Control Cyanobacterial Bloomsmentioning
confidence: 99%